Treatment Status of Patients with Β-Thalassemia Major in Northern Iran: Thalassemia Registry System - Mehrnoush KOSARYAN; Hossein KARAMI; Hadi DARVISHI-KHEZRI; Rosetta AKBARZADEH; Aily ALIASGHARIAN; Khadijeh BROMAND (Tehran University of Medical Sciences, 2019)
Background: Electronic registry system of beta-thalassemia patients was run by Thalassemia Research Center (TRC) in 2017. The aim of the current study was presentation of therapeutic status in these patients at Mazandaran Province, Iran. Methods: Therapeutic status variables including: Name of cities and hospitals, age and sex of patients, dependent and non-transfusion-dependent, starting age of the blood transfusion and iron-chelating agents, blood group and Rh, washed blood transfusion, abnormal antibody, transfusion reactions, mean hemoglobin during the last 3 months, type of iron chelators, iron chelators dosage, serum ferritin, and the use of hydroxyurea. Results: Overall, 1831 patients were registered [891 male (48.7%)]. Mean age of patients was 30±9.7 yr. Average of hemoglobin levels for female and male were 9.1±5.1 and 9.4±6.3 gr/dl, respectively. Seventy-six percent of transfusion-dependent patients (1385) have received iso-group PRBC (packed red blood cells), after crossmatch. The most common blood group among patient was type O-positive (35.7%). Monotherapy with desferrioxamine was most type of used iron-chelating agent in these patients (47.2%). Mean of ferritin was 3300±7800 (ng/ml). Twenty-eight percent of patients (484) have received hydroxyurea; proportion of male and female was approximately equal. T2 weighted magnetic resonance imaging (MRIT2*) was measured in 62.2% of patients. Moderate and severe hepatosiderosis was 10.1% and 2.9%, respectively. Patients with moderate and severe cardiac siderosis were 11% and 5%, respectively. Conclusion: Registry findings are valuable for treatment management and ensuring patients medications. It will also provide accessibility to various levels of patients' information for health care managers and experts to help them make appropriate decisions.